The EFL Students' Reading Skills in The Digital Era: What The Reading Teachers Say - Indri Anastasia; Radiatan Mardiah (Universitas Jambi, 2017)
In a time when technology is growing and changing rapidly, reading abilities remain central to students academic development. The purpose of this study is to describe the point of view of English Reading Teachers at Jambi University about EFL students reading skills in digital era based on their experience in teaching reading. The point of views covered three main topics: the reading learning outcomes, the reading learning activities, and the reading learning resources. Focus group discussion with ten reading teachers of Jambi University was used to get the data. The teachers said that the reading skills of the students are not sufficient to help them in touch with the digital era although they have digital gadget at hands. Some of the students are reluctant to read and they are lack of reading strategies, literally and critically. Effective instruction and consistent reading practice and use over long periods of time is required in order to develop the EFL students reading skills.